2021
DOI: 10.1038/s41467-021-21744-w
|View full text |Cite
|
Sign up to set email alerts
|

Hyocholic acid species as novel biomarkers for metabolic disorders

Abstract: Hyocholic acid (HCA) is a major bile acid (BA) species in the BA pool of pigs, a species known for its exceptional resistance to spontaneous development of diabetic phenotypes. HCA and its derivatives are also present in human blood and urine. We investigate whether human HCA profiles can predict the development of metabolic disorders. We find in the first cohort (n = 1107) that both obesity and diabetes are associated with lower serum concentrations of HCA species. A separate cohort study (n = 91) validates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 86 publications
(87 citation statements)
references
References 36 publications
4
83
0
Order By: Relevance
“…[ 73 , 74 , 75 ] A series of standard calibration solutions were diluted with desalted serum (depleted of BAs using activated charcoal) for the calibration curve. [ 76 ] The concentration of BA in an unknown sample was determined by comparing the unknown to calibration curve.…”
Section: Methodsmentioning
confidence: 99%
“…[ 73 , 74 , 75 ] A series of standard calibration solutions were diluted with desalted serum (depleted of BAs using activated charcoal) for the calibration curve. [ 76 ] The concentration of BA in an unknown sample was determined by comparing the unknown to calibration curve.…”
Section: Methodsmentioning
confidence: 99%
“…FXR and TGR5 signaling plays a critical role in regulating the systemic lipid, glucose, and energy homeostasis (Jiang et al, 2015;Shapiro et al, 2018). Dysregulation of systemic BA metabolism has been linked to multiple diseases, including fatty liver disease, cardiovascular disease, and type 2 diabetes (Chan & Wong, 2019;Shapiro et al, 2018;Zheng et al, 2021). Thus, the gut-microbiome-BA axis is increasingly recognized as a therapeutic target for treating metabolic and immune disorders (Chan & Wong, 2019;Gu et al, 2017;Targher et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The first use of pig bile for treatment of ‘xiao-ke’, a condition known today as diabetes, was recorded ∼400 years ago by the Chinese medical practitioners in the Compendium of Materia Medica ( Li, 1573‒1593 ). Recently, we found HCA species as novel biomarkers for metabolic diseases ( Zheng et al, 2021b ) and also identified the role of HCA species in the prevention of diabetes as well as their mechanism of action ( Zheng et al, 2021a ). Although bile acids (BAs) are mostly associated with their aid in food digestion, they have also been shown to act as signaling molecules by binding to two particular receptors, farnesoid X receptor (FXR) and the G-protein-coupled receptor TGR5.…”
mentioning
confidence: 99%